'So, you want us to be Englishmen … ': Jovellanos and British influence on Spain's first modern parliament (1808–1810). Issue 1 (2nd January 2016) - Sarasola, Ignacio Fernández
Abstract : The first modern Parliament in Spanish history held its opening session on 24 September 1810 and was known as 'Cortes de Cádiz'. It was conceived in light of the French Assemblée National pattern, as most members of Spanish liberalism admired French revolutionary political thought. However, an alternative had already been put forward. From 1808 to 1810, the most prominent character in the Spanish Enlightenment, Gaspar Melchor de Jovellanos, had tried to promote the establishment of a Spanish Assembly similar to the British parliament. Supported by two British figures, Lord Holland and John Allen, Jovellanos designed a detailed plan to introduce the British system of a 'balanced constitution' in Spain for the first time.